An empirical assessment of the short-term impacts of a reading of Deborah Zoe Laufer's drama Informed Consent on attitudes and intentions to participate in genetic research. Issue 2 (3rd April 2018) - Rothwell, Erin; Botkin, Jeffrey R.; Cheek-O'Donnell, Sydney; Wong, Bob; Case, Gretchen A.; Johnson, Erin; Matheson, Trent; Wilson, Alena; Robinson, Nicole R.; Rawlings, Jared; Horejsi, Brooke; Lopez, Ana Maria; et al.
ABSTRACT: Objective : This study assessed the short-term impact of the play "Informed Consent" by Deborah Zoe Laufer (a fictionalized look at the controversy over specimens collected from the Havasupai Tribe for diabetes research in 1989) on perceptions of trust, willingness to donate biospecimens, and attitudes toward harm and privacy among the medical and undergraduate students, faculty, and the public in the Intermountain West.Methods : Surveys were administered before and after a staged reading of the play by professional actors. Survey items included the short form Trust in Medical Researchers, and single-item questions about group identity, ethics of genetic testing in children, and willingness to donate biospecimens. In addition, respondents were given the option to answer open-ended questions through e-mail.Results : Out of the 481 who attended the play, 421 completed both the pre and post surveys, and 166 participants completed open-ended questions online approximately 1 week after the play. Across all participants, there were significant declines for trust in medical researchers and for the survey item "is it ethical for investigators to test children for adult onset diseases" ( p < .001 for both) following the play. There was a significant increase in agreement to improve group identity protections ( p < .001) and there were no differences on willingness to donate biospecimens to research ( p = .777). Qualitative data provided extensive contextual data supporting these perspectives.Discussion : This is one of the first studies to document short-term impacts of a theatrical performance on both attitudes and behavioral intentions toward research ethics and clinical research participation. Future research should continue to explore the impact of theatrical performances among public and investigators on the ethical issues and complexities in clinical research.